PENGARUH TABUNGAN WADI’AH, GIRO WADI’AH, BONUS WADI’AH, PEMBIAYAAN MUDHARABAH, DAN PEMBIAYAAN MUSYARAKAH TERHADAP LABA BANK UMUM SYARI’AH PERIODE 2014-2019 - Nurul Inayah; Anik Malikah; Abdul Wahid Mahsuni (Universitas Islam Malang, 2020)
ABSTRACT This study aims to see the effect of wadi'ah savings, wadi'ah current accounts, wadi'ah bonuses, mudharabah financing, and musyarakah financing on the profit of Islamic commercial banks for the 2014-2019 period. The population in this study is the financial statements of Syari'ah Commercial Banks registered with the Financial Services Authority (OJK) for the 2014-2019 period. The number of manufacturing companies sampled in this study were 5 syari'ah commercial banks, observations were obtained using the purposive sampling method. The data analysis technique used is multiple linear regression analysis with SPSS 20. Based on the analysis, the results of this study indicate that the results of the F test show that wadi'ah savings, wadi'ah giro, wadi'ah bonus, mudharabah financing, and musyarakah financing significant effect on the profit of Islamic commercial banks. the results of this study indicate that the results of the t test show that wadi'ah savings, musyarakah financing positive and significant effect, wadi'ah bonus negative effect on the profit of Islamic commercial banks, wadi'ah giro and mudharabah financing not significant effect on the profit of Islamic commercial banks.Key words: wadi'ah savings, wadi'ah current accounts, wadi'ah bonuses, mudharabah financing, musyarakah financing, profit.